Neoparamoeba perurans loses virulence during clonal culture - Andrew Bridle; Davenport, D; Crosbie, PBB; Polinski, M; Barbara Nowak (2015)
Amoebic Gill Disease affects farmed salmonids and is caused by Neoparamoeba perurans . Clonal cultures of this amoeba have been used for challenge experiments, however the effect of long-term culture on virulence has not been investigated. Here we show, using in vitro and in vivo methods, that a clone of N. perurans which was virulent 70 days after clonal culture lost virulence after 3 years in clonal culture. We propose that this is related either to the lack of attachment to the gills or the absence of an extracellular product, as shown by the lack of cytopathic effect on Chinook salmon embryo cells. The avirulent clonal culture of N. perurans allowed us to propose two potential virulence mechanisms/factors involved in Amoebic Gill Disease and is an invaluable tool for host-pathogen studies of Amoebic Gill Disease.